ICT-based near infrared fluorescent switch-on probe for nitric oxide bioimaging in vivo. (July 2019) - Liu, Yawei; Fan, Haoyu; Wen, Yue; Jia, Ti; Su, Qianqian; Li, Fuyou
Abstract: A cyanine dye (Cy7) based turn-on fluorescence probe has been successfully synthesized for the detection of nitric oxide through the attachment of a methyl amino group at the meso position of Cy7 dye. The probe exhibits weak fluorescent emission at 800 nm due to intramolecular charge transfer process, while it quickly turns into highly NIR fluorescent state upon the treatment with NO. The detection limit is as low as 11.3 nM. In addition, the selectivity of the probe toward NO over reactive oxygen species, reactive nitrogen species, and metal ions was also demonstrated. Importantly, the fluorescence response of this probe to NO occurs in the physiologically favorable NIR region, enabling its further use to image endogenous NO in an inflamed mouse model with low background interference and deep penetration depth. Graphical abstract: Image 1 Highlights: A cyanine dye (Cy7) based turn-on fluorescence probe has been successfully synthesized for the detection of nitric oxide. The probe shows good selectivity and low detection limit toward NO. This probe is able to image endogenous NO in an inflamed mouse model.